The The Role of Brand Trust as a Mediating Variable in The Relationship Between Brand Image and Promotion In The Decision to Choose a College - Yani, Tri Endang; Albert, Albert; Kridasusila, Andy; Santoso, Aprih; Kuswardani, DC (SENTRALISASI, 2025)
The research aims to examine the role of Brand Trust, Brand Image and promotion in the decision to choose a college. Research provides the benefit of providing input for universities in their efforts to increase the number of students. The population in this study were students who had still been active at Semarang University. The total number of samples taken was 106 respondents using purposive sampling data collection techniques. The analysis technique used is multi-linear regression and path analysis. The research results show that Brand Image and Promotion partially influence Brand Trust. Brand Image, Promotion and Brand Trust partially influence the decision to choose a university. However, Brand Trust is not able to mediate the relationship between Brand Image and the Decision to Choose a college and the relationship between Promotion and the Decision to Choose a college. The results of this research have the implication that universities can develop more targeted strategies to create a positive image of universities and design appropriate promotional strategies to increase trust in universities and increase the number of students.